Human papillomavirus vaccine uptake among teens before and during the COVID-19 pandemic in the United States - Dina K. Abouelella; Julia E. Canick; Justin M. Barnes; Rebecca L. Rohde; Tammara L. Watts; Eric Adjei Boakye; Nosayaba Osazuwa-Peters (Taylor & Francis Group, 2022)
It is unclear how the COVID-19 pandemic impacted human papillomavirus (HPV) vaccine uptake and which sociodemographic groups may have been most impacted. We aimed to assess differences in HPV vaccine uptake (initiation and completion) before and during the pandemic in the United States. We conducted a cross-sectional study using data from the 2019 to 2020 National Immunization Surveys - Teen (NIS-Teen), comparing vaccine initiation and completion rates in 2019 vs. 2020, based on confirmed reports by a healthcare provider. Weighted logistic regression analysis estimated odds of vaccine initiation and completion for both adolescent and parental characteristics. There were 18,788 adolescents in 2019 and 20,162 in 2020. There was 3.6% increase in HPV vaccine initiation (71.5% vs. 75.1%) and a 4.4% in completion (54.2% vs. 58.6%) rates from 2019 to 2020. In 2020, Non-Hispanic White teens were significantly less likely to initiate (aOR = 0.62, 95% CI: 0.49, 0.79) and complete (aOR = 0.71, 95% CI: 0.58, 0.86) vaccine uptake compared with non-Hispanic Black teens. Additionally, teens who lived above the poverty line were also less likely to initiate HPV vaccination (aOR = 0.63, 95% CI: 0.49, 0.80) or complete them (aOR = 0.73, 95% CI: 0.60, 0.90), compared to those who lived below the poverty line. During the COVID-19 pandemic in 2020, some historically advantaged socioeconomic groups such as those living above the poverty line were less likely to receive HPV vaccine. The impact of the pandemic on HPV vaccine uptake may transcend traditional access to care factors.